Pengaruh Model Pembelajaran Kooperatif Tipe Group Investigation terhadap Hasil Belajar PPKn Kelas 3 di MI Ikhwanul Muslimin - Ralisya Shaqinah Alfajriah; Muhammad Fahri; Yono Yono (Journal on Education, 2024)
Student PPKn learning outcomes are still unsatisfactory, causing students' low understanding of the material, thus affecting student learning outcomes who have not reached the Minimum Completeness Criteria (KKM) score. This research aims to determine the effect of implementing the group investigation type cooperative learning model to answer existing problems in the field. The research method used is an experimental research method. The research results show that: (1) Student learning outcomes before using the Group Investigation Cooperative Learning Model show that the average learning outcomes for experimental class students is 65.6 and the control class is 74.8. These results show that the average learning outcome for the experimental class is still below the KKM, namely 68; (2) Student Learning Results after using the Group Investigation Type Cooperative Learning Model, in this discussion the results of data analysis for the final test (posttest) between the experimental and control groups show different average values. This shows that the average learning outcome for experimental class students is 70.4 and the control class is 77.6. These results show that the two classes got an average learning outcome above the KKM, namely 68; (3) The influence of the Group Investigation type cooperative learning model on student learning outcomes. In the application of the group investigation type cooperative learning model, it can be concluded that the results of the pretest for class III A students (experiment) got a value below the average, namely 65.6, while the KKM in terms of Civics learning at school is 68. After being treated with the group investigation type cooperative learning model in this class, it can be seen that there has been an increase in learning outcomes up to 70.4. So we get a difference of 4.8.